UTILISATION OF ORGANIC WASTES IN TOMATO (Lycopersicon esculentum L.) PRODUCTION - B. ANIL KUMAR, P. SHREEMATHI, K. JEEVAN RAO, P. PRABHU PASADINI and (The Journal of Research, PJTSAU, 2017)
Waste management has become a major environmental challenge and agricultural application of organic wastes as nutrient source for plants and as soil conditioner is generally considered the best alternate option for disposal. In intensive agriculture, green manuring seems to be difficult and organic manures have become scarce due to mechanization of agriculture. So recycling of different organic wastes as composts would not only ensure the hygienic disposal of the organic wastes but also make them useful manures. The agronomic utilization of organic wastes such as urban compost, sewage sludge and biochar has been increasing because of the need to lower disposal costs. The recycling of different wastes rich in organic carbon/matter would make them useful manures and by recycling plant nutrients, improving soil fertility along with physical properties which may enhance crop yields.